1978
DOI: 10.1002/cpt197824140
|View full text |Cite
|
Sign up to set email alerts
|

Effect of smoking on caffeine clearance

Abstract: The elimination of caffeine from saliva was compared in groups of healthy smokers (n = 13) and nonsmokers (n = 13). Mean caffeine t1/2 in smokers (3.5 hr) was shorter than that in the nonsmokers (6.0 hr). The body clearance of caffeine in the smokers (155 +/- 16 ml . kg-1 . hr-1) was greater than that in the nonsmokers (94 +/- 18 ml . kg-1 . hr-1) (p less than 0.05). No significant difference was noted in the apparent volume of distribution in smokers (720 +/- 67 ml . kg-1) and nonsmokers (610 +/- 80 ml . kg-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
116
1
2

Year Published

1989
1989
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(126 citation statements)
references
References 7 publications
7
116
1
2
Order By: Relevance
“…It is possible that this may have biased the clearance values in this group although overall there was no statistical relationship between pre-study caffeine intakes and any of the pharmacokinetic variables. Caffeine clearance has been shown to increase in smokers (Parsons & Neims, 1978). In the present study, none of the patients with decompensated cirrhosis smoked and in the patients with compensated cirrhosis, no significant differences were observed in kinetic variables between the smokers and non-smokers.…”
Section: Discussioncontrasting
confidence: 60%
“…It is possible that this may have biased the clearance values in this group although overall there was no statistical relationship between pre-study caffeine intakes and any of the pharmacokinetic variables. Caffeine clearance has been shown to increase in smokers (Parsons & Neims, 1978). In the present study, none of the patients with decompensated cirrhosis smoked and in the patients with compensated cirrhosis, no significant differences were observed in kinetic variables between the smokers and non-smokers.…”
Section: Discussioncontrasting
confidence: 60%
“…The metabolism is slowed during pregnancy (Knutti et al, 1981) and in women taking oral contraceptives (Callahan et al, 1983). On the other hand, the clearance rate of caffeine is greater in smokers than in non-smokers (Parsons & Neims, 1978).…”
Section: Introductionmentioning
confidence: 88%
“…Moreover, in a cross-sectional observational study using 24 h ambulatory blood pressure monitoring, moderate smokers and coffee drinkers with mild hypertension had signi®cantly higher daytime blood pressure than nonsmokers and those who did not drink coffee (Narkiewicz et al, 1995), which suggests that the effect might recur throughout the day, despite the increased caffeine catabolism in smokers (Parsons & Neims, 1978).…”
Section: Acute Intake Of Coffee or Caffeine And Blood Pressurementioning
confidence: 99%
“…Although previous studies have shown that caffeine can enhance the reinforcing effects of nicotine (Shoaib et al, 1999;Jones and Griffiths, 2003), no study has evaluated whether nicotine enhances the reinforcing effects of caffeine. However, it is known that cigarette smoking decreases the half-life of caffeine by as much as 50% (Parsons and Neims, 1978;May et al, 1982). Thus, higher rates of caffeine consumption among cigarette smokers may be due to the faster rate of caffeine elimination.…”
Section: Effects Of Nicotine Maintenance On Intravenous Caffeinementioning
confidence: 99%